2009
DOI: 10.1093/jxb/erp328
|View full text |Cite
|
Sign up to set email alerts
|

Differential gene expression analysis provides new insights into the molecular basis of iron deficiency stress response in the citrus rootstock Poncirus trifoliata (L.) Raf.

Abstract: Iron chlorosis is one of the major abiotic stresses affecting fruit trees and other crops in calcareous soils and leads to a reduction in growth and yield. Usual remediation strategies consist of amending iron to soil, which is an expensive practice, or using tolerant cultivars, which are difficult to develop when not available. To understand the mechanisms underlying the associated physiopathy better, and thus develop new strategies to overcome the problems resulting from iron deficiency, the differential gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
28
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(33 citation statements)
references
References 47 publications
3
28
0
1
Order By: Relevance
“…Nitrogen and S assimilation-related genes were downregulated by 14-days Fe deficiency (Table 2) but not by 25-days Fe deficiency ( Table 3). Upregulation of thioredoxin/ glutaredoxin gene (Tables 2 and 3) was consistent with the previous reports that indicated that thioredoxin/ glutaredoxin is important under reducing power-starved conditions (Stenbaek et al 2008;Forner-Giner et al 2010). GSH transferases (GSTs) were also upregulated up to three-fold by Fe deficiency in the leaves (Tables 2 and 3).…”
Section: Analysis Of Microarray Datasupporting
confidence: 90%
See 1 more Smart Citation
“…Nitrogen and S assimilation-related genes were downregulated by 14-days Fe deficiency (Table 2) but not by 25-days Fe deficiency ( Table 3). Upregulation of thioredoxin/ glutaredoxin gene (Tables 2 and 3) was consistent with the previous reports that indicated that thioredoxin/ glutaredoxin is important under reducing power-starved conditions (Stenbaek et al 2008;Forner-Giner et al 2010). GSH transferases (GSTs) were also upregulated up to three-fold by Fe deficiency in the leaves (Tables 2 and 3).…”
Section: Analysis Of Microarray Datasupporting
confidence: 90%
“…The upregulation of GRXs in Fe-deficient barley leaves (Tables 2 and 3) might be important not only to overcome the limited reducing power from photosynthesis (Forner-Giner et al 2010) but also to facilitate synthesis of [Fe-S] proteins under Fe-deficient conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Catalase and peroxidase activities have been shown to be valuable indicators of the nutritional status of Fe in leaves (Baghour et al, 1999;Forner-Giner et al, 2010). In this experiment, the highest foliar activities of catalase and peroxidase (Table 3) were found in treatments T3 and T4, and the lowest in T1.…”
Section: Effect Of the Root Temperatures On The Nutritional Status Ofmentioning
confidence: 51%
“…Differential gene expression analysis has recently been reported in citrus rootstock as a new tool to understand the mechanisms underlying the Fe-de fi ciency physiopathy and to develop new screening strategies to identify chlorosistolerant citrus rootstock genotypes (Forner-Giner et al 2010 ) . With this technique, some genes induced by iron de fi ciency in Poncirus trifoliata L. have been identi fi ed, putatively involved in determining photosynthesis rate and chlorophyll content, cell wall modi fi cations and reducing oxidative stress.…”
Section: Changes In Gene Expressionmentioning
confidence: 99%